Organizational Evolution: Navigating Change and Innovation for Sustainable Development - Hasyim, Hasyim; Bakri, Muhammad (Jurnal Manajemen Bisnis, 2023)
The study aims to investigate the multifaceted dynamics of organizational evolution, focusing on the role of leadership, organizational culture, and external forces. Through a comprehensive literature review, the research explores the drivers, processes, and outcomes underlying organizational evolution. Transformational leadership and inclusive leadership styles are examined for their impact on organizational adaptability and innovation readiness. Strategic visioning, effective communication, and role modeling are identified as key leadership practices facilitating organizational adaptation and innovation. Additionally, the study highlights the interplay between leadership, organizational culture, and external factors such as technological advancements, globalization, and regulatory changes in shaping organizational evolution. Findings emphasize the importance of strategic alignment, organizational agility, and cultural agility in enabling organizations to navigate change successfully. The research contributes to understanding the mechanisms through which leadership and culture influence organizational evolution, providing insights for practitioners and scholars alike.